The Impact of the Female Advantage in Education on the Marriage Market - Ana Rodríguez-González (Lund University, School of Economics and Management, Department of Economics, 2021)
In recent years, the traditional gender gap in educational attainment in favor of men has been reversed in many countries. This development may have far-reaching consequences for the family, challenging traditional patterns of union formation and potentially affecting marriage and fertility outcomes. I study the implications of the female advantage in education on family formation through changes in the marriage market. My empirical strategy exploits the gradual implementation of a large school reform in Finland that increased women's relative level of education. I analyze the reduced-form relationship between marriage market exposure to the reform and marriage and fertility outcomes. The results show that in marriage markets with a larger female advantage in education men had fewer children and were less likely to be in a couple by age 40. I provide suggestive evidence that these results are mostly driven by the mismatch between the distributions of educational attainment of men and women, and that they might have negative consequences for low-educated men's health behaviors and mental health.
Keywords: I10; J12; J13; J16; 330; Gender gap; Education; Marriage; Fertility; Marriage market; Health